Avaliação do desempenho operacional de um convertedor LD através do desenvolvimento do processo de sopro com lança de quatro furos - Alin Junior Machado Chaves (2006)
Process BOF, is responsible for about 77% of the Brazilian steel production. The fast growth of this process in the Brazilian and world had a production must its adequate characteristics of high productivity, costs and the great metallurgic flexibility, being able economically to manufacture most of the types of steel. The development of the process in less than three decades of existence, the basic principles practically remain constant. However, considerable developments had been effected, in that it not only says respect to the capacity of the BOF, that today reaches values of the order of 400 tons, but also in its form, devices of sustentation and tilting, in the form and number of nozzle for oxygen blow, to the side of the improvement of the operational techniques. With adjusted applications of blow, almost all the refining reactions can be gotten. This characteristic, allied to the favorable conditions of costs, as much of investment how much operational they had been responsible for the fast evolution of the participation of process BOF in the world steel production. Through the lance oxygen of high pureness with supersonic speed on the surface of the scrap is blown. A region of impact of the spurt, highest temperatures is created there, giving beginning to the reactions of refining and the formation of the slag. The time of duration of the blow depends on the project of the lance nozzle and of the outflow of work oxygen, being able to be it enters the 10 30 minutes. To improve the operational performance of convertedor LD of would aciaria of the Belgo, Monlevade plant, through the development of the process in the use of the lance of four hole is the objective of this work, being evaluated through the following results, having as reference the values gotten currently with the spear of three punctures: Time blowMetallic Metallic yeld FeO of the slag Temperature blow end. It was elaborated an experiment plan having involved two stages, where blow pattern of blow for lance of four hole had been developed and had been manufactured heats of four hole compared with the heats manufactured with the lance of three holes. The preliminary results had shown to be viable the use of the lance of four hole, therefore performance in the too much parameters the same had a reduction in the time of blow in average of two minutes and keeping (metallic yeld, FeO of the slag, temperature blow end).